Numerical and Experimental Study of Flows with Variable Density - Khorshid, Sepideh (Université d'Ottawa / University of Ottawa, 2019)
The knowledge of density current behaviours as a result of two or more fluids of different densities interacting is of particular importance in many practical applications. Within the field of hydraulic engineering, examples include buoyant effluent discharges from desalination plants, advancements of saline water under freshwater in estuaries, and flows occurring when a gate is removed at the outflow/inflow of a river. The main goal of this study is to improve the understanding of the mixing patterns of density currents as well as their related numerical simulation. In this study, first, an advanced numerical solver for 2D variable-density shallow water equations is developed and validated where both well balanced and positivity preserving properties are achieved over an unstructured grid. The improved numerical scheme is flexible, and accounts for flooding over irregular bed topographies by using a triangular grid. Second, a numerical study of two-layer stratified flows over an isolated submerged dune is conducted. This part focuses on modeling density currents created when a narrow channel connects two water bodies with different densities and a stratified two-layer flow is subsequently generated. A 3D Large Eddy Simulation (LES) model is developed in OpenFoam and validated with the experimental data to investigate the flow patterns and entrainment. In addition to the LES model, a RANS numerical model is also used, and the results are compared in order to prove the superiority of the LES method in modeling complex mixing behaviours. LES predictions showed good agreement with the experimental measurements, as the LES model was able to capture the KH instabilities. In the third part of this study, the interaction between inclined negatively buoyant jets and waves, such as in the case of brine discharges from desalination plants into the ocean, is experimentally investigated. In addition to discharges in a wave environment, experiments are also performed in a stagnant environment and a wave-current environment in order to compare the results. A combination of the Particle Image Velocimetry (PIV) technique and the full-field Laser Induced Fluorescence (LIF) technique is employed to reveal the mixing patterns. The results showed that the wave motion affects the inclined negatively buoyant jet geometry, resulting in the jet’s rotation and an increase in its width. This study led to derivation of empirical formulae calculating terminal rise height and minimum dilution at specific points. In the fourth part, the numerical simulations of 45° inclined dense jets in wavy ambient have been conducted using a finite volume model (OpenFOAM). The selected turbulence models include RNG k-ε, realizable k-ε; Nonlinear k-ε; and LRR. The results of this study are compared to the results from experimental investigations in the third part and comparative figures and tables are presented and discussed. It has been observed that the LRR turbulence model as well as the realizable k-ε model predict the flow more accurately among the various turbulence models studied herein.
Keywords: Variable Density